An axiomatic analysis of ranking sets under simple categorization - José C. R. Alcantud; Ritxar Arlegi (SERIEs - Journal of the Spanish Economic Association, 2012)
This paper contributes to the axiomatization of additive rules for ranking sets of objects under the psychological principle of categorization. Firstly we proceed with the case where the elements in the sets are categorized into at most three groups, namely good (with value 1), neutral (with value 0), and bad (with value-1). Secondly, we solve the case where there are only good and neutral elements. In both instances the evaluation of the sets is purely additive. Lastly, we show that dropping one of the axioms in our general characterization produces an axiomatization of the more general class of evaluations where good and bad elements are weighted differently. Areas of research in Economics such as committee selection problems, hedonic games and matching are among the ranking sets models where our results could potentially be applied.
Keywords: D01; D71; D81; 330; ranking sets; additive representation; categorization; Entscheidungstheorie; Ranking-Verfahren; Neue politische Ökonomie